Selectivity, Favoritism, and Performance: The Role of Investment Consultants in Private Equity - Martinez, Jose Vicente; Qian, Yiming (The Review of Corporate Finance Studies, 2026)
We examine the influence of consultants on the portfolio choices and performance of institutional asset owners’ private equity (PE) investments. We find that asset owners using the same search consultant make similar investment choices. Asset owners advised by consultants that focus on a narrower list of PE managers perform better. Among asset owners that share a consultant, those with the largest PE mandates (top clients) end up with better-performing investments. For mechanisms underlying consultants’ performance impact, we find evidence for both access and selection abilities. (JEL G11, G20, G23)